Cloning and characterization of the gene encoding glyceraldehyde-3- phosphate dehydrogenase from coconut (Cocos nucifera L.) - Regalado, Ellen S.; Angeles, Jorge Gil C.; Rodelas, Abigail Joy D.; Garcia, Roberta N.; Laurena, Antonio C.; Tecson-Mendoza, Evelyn Mae (2008)
Reverse Transcription-Polymerase Chain Reaction (RT-PCR) strategy was employed to clone the gene encoding glyceraldehyde-3-phosphate dehydrogenase (Gap) in coconut using a gene specific 20-mer primer pair. The sense primer had a 45.3 C melting temperature (Tm) and 50% Guanine-Cytosine (GC) content. The antisense primer, on the other hand, had a 48.3 C Tm, 50% GC and a G repeat in it. A modified Invitrogen's one-step TOPO-TA Cloning Kit was used to insert the 845 bp PCR product into a TOPO vector. The 845 bp PCR product was used in the transformation of E. coli DH5a. Two positive clones (H3 and H23) were sequenced. The partial cDNA sequence of the H3 clone (designated as cocoGapC1) contained 669 nucleotides with an open reading frame (ORF) encoding 222 amino acids, corresponding to a 24.4Kda polypeptide. Sequence alignment revealed that it had 72.9% nucleotide sequence homology and a 95.6% amino acid homology with the Gap genes of other plant species. The partial cDNA sequence of the H23 clone (designated as cocoGapC2) was composed of only 649 nucleotides with an ORF that encoded a polypeptide of 216 amino acid with 24.2KDa molecular weight. Alignment with other plant Gap sequences showed that it had a 72.6% nucleotide sequence homology and a 95.9% amino acid homology. Regions associated with the metabolite function of NAD-Gap were noted on both cocoGapC1 and C2-deduced amino acid sequences. These regions included the putative NAD-binding domain from Thr-3 to Ala-114 and the putative catalytic-binding domain from Val-115 to Val-173. Alignment of the nucleotide and amino acid sequences of cocoGapC1 and C2 revealed percent identities below 95% (89.1% and 72.5%, respectively) due to the differences in length of the sequences. CocoGapC1 is longer by about 20 bp than cocoGapC2 with only 649 bp.
Keywords: Coconut; Proteins; Cloning